Lama Hari Rawat Pasien Stroke - Novita Nirmalasari; Muhamat Nofiyanto; Rizqi Wahyu Hidayati (Poltekkes Kemenkes Surakarta, 2020)
Background: Stroke has remained the leading cause of death globally in the last 15 years. Stroke is rapidly developing clinical signs of focal or global disturbance of cerebral function. Hospitalization is a treatment process which including patient to stay at the hospital. Length of stay is influenced by the type of stroke. This study aimed to know classification of stroke and length of stay of stroke patients. Methods: The study was a descriptive study with restrospective design. Data collected from medical record from May until December 2020 in RS PKU Muhammadiyah Yogyakarta. There were 207 patients with stroke. Descriptive data is then processed. Results: The results showed the highest percentage stroke patients male (50,24%), non hemorrhagic stroke (57,49%), length of stay hemorrhagic stroke 8 days. Conclusion: The result of this study may provide nursing research in patients with stroke.